2019
DOI: 10.1001/jamanetworkopen.2019.17257
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Regional Brain Structural Differences With Aging, Modifiable Risk Factors for Dementia, and Cognitive Performance

Abstract: IMPORTANCE Identifying brain regions associated with risk factors for dementia could guide mechanistic understanding of risk factors associated with Alzheimer disease (AD). OBJECTIVES To characterize volume changes in brain regions associated with aging and modifiable risk factors for dementia (MRFD) and to test whether volume differences in these regions are associated with cognitive performance. DESIGN, SETTING, AND PARTICIPANTS This cross-sectional study used data from UK Biobank participants who underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 66 publications
1
27
0
Order By: Relevance
“…Alternatively, our stringent multiple testing corrections to guard against false positives can potentially cause some true positives to be missed; a limitation of the approach. Analysis showed associations between higher brain age difference and type I and type II diabetes, a finding previously observed in other imaging studies 33 including analysis on UK biobank 10 and supported by previously recognised effects of diabetes on brain structure 34 , 35 . This study also revealed a direct association between brain age differences and vascular disease risk factors, particularly blood pressure.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Alternatively, our stringent multiple testing corrections to guard against false positives can potentially cause some true positives to be missed; a limitation of the approach. Analysis showed associations between higher brain age difference and type I and type II diabetes, a finding previously observed in other imaging studies 33 including analysis on UK biobank 10 and supported by previously recognised effects of diabetes on brain structure 34 , 35 . This study also revealed a direct association between brain age differences and vascular disease risk factors, particularly blood pressure.…”
Section: Discussionsupporting
confidence: 79%
“…Associations between brain age deviations using distinct approaches to ours but similar data from UK biobank also revealed associated between this phenotype and blood pressure adding internal validity to these results 10 . Although a relationship between hypertension and both cognitive decline and brain atrophy has already been established 35 , 36 , and prolonged hypertension is recognised to be associated with increased white matter pathology 37 , 38 the mechanisms of these associations are not well defined 39 . Physical fitness was associated with lower brain age difference highlighting the association of physical fitness not only to functional 40 , but also to structural changes of the brain.…”
Section: Discussionmentioning
confidence: 99%
“…The brain areas with associated iron deposition in p.C282Y homozygote men included the hippocampus and thalamus, two structures known to play important roles in memory function [ 23 ], and which are frequently affected in early Alzheimer’s disease [ 24 ], as well as in the putamen, where iron accumulation occurs with aging [ 25 ] and in geriatric depression [ 26 ]. Smaller putamen gray matter volumes have been reported in neurodegenerative disorders [ 27 ], including Alzheimer’s disease [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, our observations may also reflect interactions between pathologies across organ systems. For example, alcohol is metabolized primarily in the liver, where it increases fatty acid synthesis(6) and leads to metabolic abnormalities that independently contribute to cardiovascular and brain pathologies(55-57).…”
Section: Discussionmentioning
confidence: 99%